Sustainability and the Olympic Games : A Marketing Strategy or a Genuine Goal? - Corea Gonzalez, Jorge Adalberto; Kania, Karolina Anna; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates how sustainability initiatives at the Olympic Games have evolved and shaped public perception and institutional credibility, focusing on London 2012, Rio 2016, and Paris 2024. Using a qualitative comparative case study approach, it analyzes official documents, media reports and semi-structured interviews to examine the gap between sustainability rhetoric and delivery. The research reveals a shift from operational implementation to strategic branding, with recurring contradictions such as Paris’s carbon neutrality claim undermined by the carbon-intensive Tahiti surfing event. While London 2012 pioneered formal standards like ISO 20121, Rio 2016 struggled with its environmental ambitions, and Paris 2024 introduced advanced carbon budgeting. This study contributes to sporting mega event scholarship by integrating legacy theory with public perception data. It recommends mandatory post-Games audits, Community Benefit Agreements, and SDG-aligned planning to ensure accountability and inclusive legacy outcomes for future Olympic hosts.
Vedoucí práce: Karolina Anna Kania
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses